Simplify 8/-3 divided by -4/9

1 answer

To divide fractions, we can multiply by the reciprocal of the second fraction.
So, (8/-3) ÷ (-4/9) is the same as (8/-3) * (9/-4).

Multiplying the numerators, we get: 8 * 9 = 72.
Multiplying the denominators, we get: -3 * -4 = 12.

Therefore, (8/-3) ÷ (-4/9) simplifies to 72/12.

To further simplify, we can divide both the numerator and denominator by their greatest common divisor, which is 12.

72 ÷ 12 = 6
12 ÷ 12 = 1

So, the simplified form of the expression is 6/1, which is equal to 6.